The Impact of the Treffinger Model of Developmental Organization on the Production of Creative Ideas Among Female Students at the Institute of Fine Arts in the Subject of Design Techniques - Muhammad, Israa Qasim; Al-Sakani , Suhad Jawad Faraj; Ahmed, Salah Al-Din Qadir (Journal of Ecohumanism, 2024)
Neglecting creative abilities causes societies to fall behind, emphasizing the need for modern societies to develop and flourish by adopting original ideas to solve problems. This study aimed to examine the effect of using the Treffinger model of developmental organization on the production of creative ideas among female students of the Art Institute in the field of design techniques, particularly in interior design. The model was applied through teaching plans designed according to the model and compared to traditional methods on a sample of female students to measure the impact. The research sample consisted of female students from the Institute of Fine Arts, carefully selected to ensure accurate representation of the study population. An experimental design with two equal groups was adopted to compare the effect before and after. The results showed noticeable differences in the creative performance of female students who studied according to the Treffinger model compared to the traditional method, highlighting the model's effectiveness in enhancing creative abilities. Accordingly, the researcher recommended adopting this model in the educational process in general and in fine arts institutes in particular, and suggested further applied studies to generalize the benefits of this model.